Analisis Kinerja Keuangan Pt Summarecon Agung Tbk Dan Pt Pakuwon Jati Dengan Menggunakan Metode Du Pont System Dan Analisis Economic Value Added (Eva) Periode 2015-2017 - Esterlina Angela Juliana (Universitas Tarumanagara, 2019)
Research at PT Summarecon Agung Tbk and PT Pakuwon Jati Tbk, located in Jakarta, aims to assess the financial performance of PT Summarecon Agung Tbk and PT Pakuwon Jati Tbk 2015-2017. The analytical method uses in this research is Du Pont System and Economic Value Added (EVA). Du Pont System is an analysis system intended to show relation between return on investment, net profit margin, and total asset turnover. Economic Value Added (EVA) is an additional value to shareholders by management in a certain period. The result of the calculation of the financial performance of PT Summarecon Agung Tbk year period 2015-2017 with the Du Pont System shows a positive value and tend to increase per year. And for the analysis method of Economic Value Added shows value fluctuation also decrease per year. As for the analysis using the EVA method, the fluctuating value also decreases per year. The results of the calculation of the performance of PT Pakuwon Jati Tbk period in 2015-2017 with Du Pont System showed a positive value and experienced an increase and decrease every year. As for the analysis using the EVA method, the value of fluctuations also decrease and increase every year. In this case, the company needs to improve the efficiency of the company, both PT Summarecon Agung Tbk and PT Pakuwon Jati in utilizing capital and managing assets owned by the company